La posición de los contrarios en la ciencia médica en Averroes. The position of contraries in the medical science of Averroes - Mesbahi, Mohamed (Anaquel de Estudios Árabes, 2006)
The theory of contrariety has been one of the essential medical theories that constitute the medicine of Ibn Rushd. Medicine aims to recuperate the balance between fundamental contraries and humors, that is, to return the human body its “moderate temperament”. If the first part of medicine, the preservation of health, employs the principle of similarity, the second part, the making of health, is based on the principle of contrariety. Ibn Rushd considers the contrariety procedure as an essential – not accidental - method, and in doing so he recognizes man´s ability to understand and influence nature.